The symbolic function in language development in children of initial II (4 years) - Maldonado Silva , Gabriela; Jiménez Sánchez, Cecilia; López Bravo , Oswaldo (Revista Universidad de Guayaquil, 2017)
The preschool age represents one of the most significant stages in the psychological development of the infant. In this age new psychological formations emerge as psychological skills of preparation of the child for their subsequent entry into school, which induce the infant to undergo substantial changes in their cognitive development and personality. The symbolic function, in this age, refers to the capacity of the infant to represent absent objects through the use of symbols and signs, according to their psychological age and sociocultural environment in which they develop. Seen in another way, the development of the symbolic function contributes, in turn, to the development of other psychological functions that are fundamental to school activity. In this context, the aim of the present study is to present a complete review of literature focusing on studies and theories about the importance of the symbolic function in the development of language in children of initial education, sub-level II; for this, the methodology used is qualitative, descriptive given that the review and description of topics focused on these research variables was carried out